1987
DOI: 10.1177/026624268700500405
|View full text |Cite
|
Sign up to set email alerts
|

Ambition and Achievement: A Study of Small Retailers

Abstract: The authors of this paper are employed at Ealing College of Higher Education, London, England, in the School of Business and Management. Pat Armstrong is the Head of Division of Applied Behavioural Science, Alison Baker is a Senior Lecturer in Sociology, currently on secondment to the CNAA, and James Johnson is a Research Assistant. The paper is based on empirical research, undertaken in the London Borough of Ealing, and was designed to investigate perceptions held by small retail proprietors of business succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The authors argued that these characteristics cannot be developed in "asocial" intellectual exercises and then applied to the social situation. Armstrong et al (1987) supported this view when they observed that only 20 percent of their sample believed their previous education was relevant to running their businesses.…”
Section: Introductionmentioning
confidence: 93%
“…The authors argued that these characteristics cannot be developed in "asocial" intellectual exercises and then applied to the social situation. Armstrong et al (1987) supported this view when they observed that only 20 percent of their sample believed their previous education was relevant to running their businesses.…”
Section: Introductionmentioning
confidence: 93%